2017
DOI: 10.5194/esd-2017-58
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Equatorial Atlantic interannual variability and its relation to dynamic and thermodynamic processes

Abstract: Abstract. The contributions of the dynamic and thermodynamic forcing to the interannual variability of the Equatorial Atlantic sea surface temperature are investigated using a set of interannual regional simulations of the Tropical Atlantic Ocean. The ocean model is forced with an interactive atmospheric boundary layer, avoiding damping toward prescribed air-temperature as is usually the case in forced ocean models. The model successfully reproduces a large fraction (R2 = 0.55) of the observed interannual vari… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 3 publications
2
14
0
Order By: Relevance
“…Our results from the heat budget analysis, confirm that air‐sea fluxes are the main drivers of the HS branches and southwestern lobe of the Atlantic Niño mode. Furthermore, we provide further evidence of the fundamental role of ocean dynamics to generate and modulate the equatorial SST variability (Dippe et al, ; Foltz et al, ; Jouanno et al, ; Polo et al, ). It is noteworthy that both thermocline and advective feedback have a substantial contribution in the development of the Atlantic Niño warm tongue, while thermocline feedback appears as dominant in the generation of the HS pattern.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…Our results from the heat budget analysis, confirm that air‐sea fluxes are the main drivers of the HS branches and southwestern lobe of the Atlantic Niño mode. Furthermore, we provide further evidence of the fundamental role of ocean dynamics to generate and modulate the equatorial SST variability (Dippe et al, ; Foltz et al, ; Jouanno et al, ; Polo et al, ). It is noteworthy that both thermocline and advective feedback have a substantial contribution in the development of the Atlantic Niño warm tongue, while thermocline feedback appears as dominant in the generation of the HS pattern.…”
Section: Resultssupporting
confidence: 61%
“…This disagrees with the results from Nnamchi et al (); (), which claimed for the thermodynamic origin of the Atlantic Niño. However, Nnamchi et al () findings are based on coupled climate models that present a strong bias in their oceanic component (Wang et al, ), causing an overestimation of the thermodynamic contribution (Jouanno et al, ). On its part, Nnamchi et al () study of reanalysis datasets is based in an approximated estimation of a not‐closed heat budget analysis, in which the air‐sea fluxes present a significant but not unique contribution to the mixed layer temperature trend (Nnamchi et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main consequence of the equatorially enhanced turbulence below the mixing layer, both in the tropical Atlantic and Pacific, is the strongly enhanced diapycnal fluxes of heat, freshwater, and nutrients that contribute to controlling the mean state and variability of SST, SSS, and primary production (e.g., Gregg et al, ; Hummels et al, ; Moum et al, ; Sandel et al, ; Schlundt et al, ; Wang & McPhaden, ). Furthermore, the results from the measurement program verified results from model studies that had shown elevated mixing to occur within the ACT region along with consequences for the heat and freshwater budget of the ACT and the Gulf of Guinea region (Camara et al, ; Da‐Allada et al, , , ; Jouanno et al, , ; Planton et al, ).…”
Section: Additional Results In Cooperation With Other National and Insupporting
confidence: 62%
“…Warm DT10A extend further south continuously up to around 25°S, corresponding to the approximate maximum latitude where the signature of Benguela Niños and corresponding interannual CTWs can be tracked (Bachèlery et al, ). The warm T10 anomaly with values greater than 0.5 °C extends northwestward into the eastern equatorial Atlantic region up to 15°W, a region with a strong seasonal cycle of SST (the seasonal formation of the Atlantic Cold Tongue) which is modulated interannually by the so‐called Atlantic Equatorial Mode often referred to Atlantic Niño with peak variability in Austral winter (Jouanno et al, , ; Lübbecke et al, ). The wind stress anomalies during the mature phase of the selected extreme events reveal persisting northerly anomalies over the warm areas along the Angolan coast.…”
Section: Resultsmentioning
confidence: 99%